2014
DOI: 10.4103/0974-2727.141507
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value and Accuracy of Conjunctival Impression Cytology, Dry Eye Symptomatology, and Routine Tear Function Tests in Computer Users

Abstract: Aims and Objectives:To compare the diagnostic value and accuracy of dry eye scoring system (DESS), conjunctival impression cytology (CIC), tear film breakup time (TBUT), and Schirmer's test in computer users.Methods:A case–control study was done at two referral eye centers. Eyes of 344 computer users were compared to 371 eyes of age and sex matched controls. Dry eye questionnaire (DESS) was administered to both groups and they further underwent measurement of TBUT, Schirmer's, and CIC. Correlation analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…The authors concluded that tear film tests should be used in combination with dry eye questionnaire for a more accurate dry eye evaluation. The present study found that CIC and DESS hold good diagnostic accuracy for dry eye evaluation in patients with psoriasis [15].…”
Section: Bhargava Et Al Compared Diagnostic Accuracy Of Cic Tbut Andsupporting
confidence: 57%
See 1 more Smart Citation
“…The authors concluded that tear film tests should be used in combination with dry eye questionnaire for a more accurate dry eye evaluation. The present study found that CIC and DESS hold good diagnostic accuracy for dry eye evaluation in patients with psoriasis [15].…”
Section: Bhargava Et Al Compared Diagnostic Accuracy Of Cic Tbut Andsupporting
confidence: 57%
“…Power was calculated using DESS to detect clinical significance between cases and controls after data analysis, based on data from previously published study [15]. Taking a lead from this study, power was calculated using primary outcome measure (DESS) and assumptions were as follows: Odds ratio = 9.8, exposed controls= 29%, one-sided alpha risk = 5%, controls / case ratio = 1.07, total exposed=48.3086%, Estimated power= 99.9999%.…”
Section: Power Calculationmentioning
confidence: 99%
“…In our study, there was no correlation between TFBUT and the DESS score. However, a study in young adults (25-26 years of age) showed that symptom-based screening using DESS was statistically associated with TBUT (Bhargava et al 2014). One reason for the difference in findings between the age groups may be the limited ability of young children to accurately express the degree and frequency of dry eye symptoms required for the DESS.…”
Section: Discussionmentioning
confidence: 99%
“…Dryness and associated symptoms in otherwise healthy eyes are commonly encountered by visual display unit users and have been cited by many investigators. Questionnaire studies have reported that the severity of dry eye is affected by the duration of computer use . Additionally, use of air‐conditioning and forced‐air heating in office environments may contribute to dryness symptoms …”
Section: Symptoms and Risk Factorsmentioning
confidence: 99%